TOOTH MORPHOTYPES SHED LIGHT ON THE PALEOBIODIVERSITY OF MIDDLE TRIASSIC TERRESTRIAL VERTEBRATE ECOSYSTEMS FROM NE IBERIAN PENINSULA (SOUTHWESTERN EUROPE) - MARC RICCETTO; EUDALD MUJAL; ARNAU BOLET; CHABIER DE JAIME-SOGUERO; SOLEDAD DE ESTEBAN-TRIVIGNO; Josep Fortuny (Rivista Italiana di Paleontologia e Stratigrafia)
The Early to Middle Triassic is a key time interval in tetrapod evolution. After the end-Permian biotic crisis, harsh environmental conditions due to global warming and aridity persisted during the Early Triassic. This led to an impoverished biodiversity, especially in equatorial Pangea, until the Middle Triassic, when vertebrate ecosystems re-flourished. The terrestrial European record is characterized by tetrapod communities dominated by temnospondyls and archosauromorphs, followed by a limited presence of lepidosauromorphs, procolophonomorphs and therapsids. Ongoing paleontological sampling at the Anisian Buntsandstein facies of northeastern Iberian Peninsula (southwestern Europe) provides new insights on the vertebrate biodiversity at equatorial paleolatitudes. The Montseny area (Catalan Coastal Ranges) has delivered moderately abundant cranial and postcranial remains in the last decades. Among the known record, dental, mandibular and skull remains are particularly relevant because they provide information on the dietary habits of the concerned taxa. In the present work, eight tooth morphotypes have been identified: two correspond to a capitosaur temnospondyl, one to an archosauromorph, one to an indeterminate diapsid and four to a procolophonid, the latter material referred to a single new taxon, Kapes signus sp. nov. These finds help to fill a gap in the lower Middle Triassic vertebrate biodiversity and distribution in present-day southwestern Europe. Based on dentognathic remains, the oldest Middle Triassic terrestrial tetrapod ecosystems from northeastern Iberia were dominated by capitosaur temnospondyls, followed by much less abundant archosauromorphs, procolophonids and indeterminate diapsids. This contrast with the ichnotaxonomical composition of the study area, denoting paleoenvironmental and/or taphonomic biases in the dental and osteological record.